2007
DOI: 10.2146/ajhp060281
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary team for enhancing care for patients with acute myocardial infarction or heart failure

Abstract: A multidisciplinary team that included pharmacists improved JCAHO core measures for hospitalized patients with MI or HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…As adherence to performance measures begins to affect reimbursement, institutions use clinical pathways and guideline‐based order sets. Pathways developed and implemented by multidisciplinary teams, including physicians, nonphysician providers, nurses, and pharmacists, have been shown to improve adherence to performance measures, medication safety, and outcomes . Clinical pharmacists can provide recommendations about drug dosing and monitoring parameters built into the order set, and implementation strategies.…”
Section: Clinical Pharmacist Roles Across the Continuum Of Heart Failmentioning
confidence: 99%
“…As adherence to performance measures begins to affect reimbursement, institutions use clinical pathways and guideline‐based order sets. Pathways developed and implemented by multidisciplinary teams, including physicians, nonphysician providers, nurses, and pharmacists, have been shown to improve adherence to performance measures, medication safety, and outcomes . Clinical pharmacists can provide recommendations about drug dosing and monitoring parameters built into the order set, and implementation strategies.…”
Section: Clinical Pharmacist Roles Across the Continuum Of Heart Failmentioning
confidence: 99%
“…These fi ndings are similar to a study in which compliance with discharge instructions remained lower than anticipated because of documentation issues within the medication reconciliation process. 4 Changes in the discharge medication transcription process at our institution are currently in process to address this systematic problem.…”
Section: Discussionmentioning
confidence: 99%
“…A single study found that a multidisciplinary team that included pharmacists may improve Joint Commission core measures for hospitalized patients with HF. 14 Due to documentation issues related to medication reconciliation, the percentage of discharge instructions remained lower than anticipated. 14 Warden et al 15 found that pharmacist involvement in medication reconciliation and discharge counseling for HF patients was associated with a significant increase in adherence to Joint Commission discharge instructions (83% vs 100%, p = 0.007).…”
Section: Introductionmentioning
confidence: 94%